Customizing hybrid products - Benford, Steve; Koleva, Boriana; Preston, William; Angus, Alice; Thorn, Emily-Clare; Glover, Kevin (2018)
We explore how the convergence of the digital and physical into hybrid products leads to new possibilities for customization. We report on a technology probe, a hybrid advent calendar with both paper form and digital layers of content, both of which were designed to be customizable. We reveal how over two hundred active users adapted its physical and digital aspects in various ways, some anticipated and familiar, but others surprising. This leads us to contribute concepts to help understand and design for hybrid customization – the idea of broad customization spanning physical and digital; end-to-end customization by different stakeholders along the value chain for a product; and the combination of these into customization maps.